Bioassay-Guided Fractionation of Acetone and Methanol Extracts of Quercus infectoria Galls with Antimalarial Properties - Nurul Hammizah Hamidon,; Anjana Chamilka Thuduhenage Dona ,; Nik Nor Imam Nik Mat Zin,; Nurul Izza Nordin,; Shaida Fariza Sulaiman,; Nurhidanatasha Abu-Bakar, (Tropical Life Sciences Research, 2024)
The antimalarial properties of crude extracts from Quercus infectoria galls were investigated through bioassay-guided fractionation. Acetone (QIA) and methanol (QIM) crude extracts have been reported to have promising antimalarial activity against Plasmodium falciparum (3D7 strain). These extracts were subjected to fractionation using automated preparative high-performance liquid chromatography (prep-HPLC) to identify the most active fractions. Nine fractions were isolated from each extract, of which the fractions QIA11 and QIM16 showed antimalarial activity, with IC50 values of 17.65 ± 1.82 ?g/mL and 24.21 ± 1.88 ?g/mL, respectively. In comparison, the standard antimalarial drug artemisinin has an IC50 value of 0.004 ± 0.001 ?g/mL). Through high-resolution liquid chromatography coupled with mass spectrometry (HR-LCMS) analysis of the fractions, four known compounds were successfully identified: gallic acid, ellagic acid, 1,3,6-tris-o-(3,4,5- trihydroxybenzoyl)-beta-d-glucose and 1-O,6-O-digalloyl-beta-D-glucose.